2002
DOI: 10.1149/1.1452116
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Co-Ni Alloys for Microsystems Applications

Abstract: A chloride plating bath, containing boric acid and saccharin has been optimized to obtain homogeneous Co-Ni deposits over normalSi/SiO2/normalTi/normalNi substrate. The goal is to explore the synergy of these layers in microsystems applications. Anomalous codeposition occurs and both electrochemical and structural results indicate that obtained Co-Ni layers correspond to solid solutions of face-centered cubic (fcc) structure, whose composition may be varied as a function of the electrodeposition parameters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…Changes observed both in morphology and structure of CoNi deposits prepared in presence of DTAC respect to those obtained in absence of additive were not consequence of the composition variation. In DTAC absence, independently of the alloy composition, the obtained CoNi deposits corresponded to a similar structure and morphology [12,13].…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Changes observed both in morphology and structure of CoNi deposits prepared in presence of DTAC respect to those obtained in absence of additive were not consequence of the composition variation. In DTAC absence, independently of the alloy composition, the obtained CoNi deposits corresponded to a similar structure and morphology [12,13].…”
Section: Resultsmentioning
confidence: 82%
“…In our laboratory, a chloride electrodeposition bath useful to prepare magnetic CoNi deposits was developed [12][13][14]. Good adherence, brilliant aspect, smooth surface and a constant deposition rate were obtained in all tested substrata.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Investigations on electrodeposited Ni-Co alloys have indicated that their properties strongly depend on the cobalt content. [3,4] Nickel-cobalt deposition belongs to the anomalous type, which means that deposition of the less noble metal (Co) in a twocomponent alloy is greatly favoured.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Nickel-cobalt deposition belongs to the anomalous type, which means that deposition of the less noble metal (Co) in a twocomponent alloy is greatly favoured. [2,5,6] There are several researchers explaining the above anomalous phenomena, with the competition adsorption of metal hydroxides, monohydroxides, or metal ions since the hydrogen evolution reaction resulted in local increase in pH near deposit-electrolyte interface. [1,7 -9] The electrolytic coating of powder particles could achieve great importance in powder metallurgy as it is one of the processes that give the best homogeneity of the final product.…”
Section: Introductionmentioning
confidence: 99%
“…electrocatalytic activities, etc. [20,21]. For instance, Au nanoparticles were found to possess extraordinary electrocatalytic activity towards many reactions, while the bulk Au electrodes showed much less or even fairly poor electrocatalytic activity towards the same reactions [22].…”
Section: Introductionmentioning
confidence: 99%